Re-endothelialization of biological tissue-engineered conduits and scaffold for its potential use in bioprosthesis. Issue 1 (2013) - Almelkar, SI; Kadam, SS; Diwate, S; Chaukar, A; Bhonde, RR; Patwardhan, AM
No abstract available